Fatal [compact disc, unabridged] : a novel - Lescroart, John T. (Simon & Schuster Audio, 2017)
Kate loves her life. At forty-four, she's happily married to her kind husband, Ron, blessed with two wonderful children, and has a beautiful home in San Francisco. Everything changes, however, when she and Ron attend a dinner party and meet another couple, Peter and Jill. Kate and Peter only exchange a few pleasant words but that night, in bed with her husband, Kate is suddenly overcome with a burning desire for Peter. What begins as an innocent crush soon develops into a dangerous obsession and Kate's fixation on Peter results in one intense, passionate encounter between the two. Confident that her life can now go back to normal, Kate never considers that Peter may not be so willing to move on.